INVESTIGATIONS OF FORCES, POWER AND SURFACE ROUGHNESS IN HARD TURNING WITH MIXED CERAMIC TOOL - Bhemuni, Varaprasad (Journal of Advanced Manufacturing Technology (JAMT), 2016)
Hard turning has been explored as an alternative to cylindrical grinding used in manufacturing parts made of tool steels. In the present study, the effects of cutting speed, feed rate and Depth of Cut (DOC) on cutting forces, specific cutting force, power and surface roughness in the hard turning are experimentally investigated. Experiments are carried out using mixed ceramic(Al2O3+TiC) cutting tool of corner radius 0.8mm, in turning operations on AISI D3 tool steel, heat treated to a hardness of 62 HRC. Response Surface Methodology (RSM) based Central Composite Design (CCD) in Design of Experiments (DOE), is adopted in deciding the number of experiments (20) to be performed with various combinations of input parameters. The range of each one of the three parameters is set at three different levels, namely low, medium and high. The validity of the model is checked by Analysis of variance (ANOVA), predicted models are derived from regression analysis. From the results most favorable parameter setting for superior surface finish is acquired at a medium speed of cutting, medium feed and low DOC.